Effect of crossfit-trainings on the heart rate of adolescent judokas - Avetisyan, Arman (Journal of Sports Medicine and Therapy, 2022)
Background: One of the types of the complex control system is medico-biological, which includes a set of methods and measures aimed at assessing the health, and functional state of the athlete’s body, taking into account the reaction of his systems to various loads. CrossFit is a constantly varied and high-intensity functional training program in which with increasing the training load, the pulse rate increases. The context and purpose of the study: The research was aimed to find out the frequency of heart rate of adolescent judokas in the presence of CrossFit-trainings in the process of physical fitness, for which a pedagogical scientific experiment was held at the youth sports and cultural training center after V. Zakaryan (Hrazdan city). From the groups of 10-12-year-olds practicing judo at the sports school, one experimental and control group was formed, each with 10 athletes. During CrossFit-trainings “Tabata”, “AMRAP”, “21-15-9” and “WOD” methods were mainly used. Athletes’ pulse rate was measured manually at the wrist before training, during training, and immediately after training in order to control the athletes’ feelings toward the training load. Results: In the September-June period, with the implementation of the CrossFit-training program, the heart rate of athletes before training was on average 102,2 bpm, during training 158,3 bpm and immediately after training – 157,8 bpm. Conclusion: The indicators obtained as a result of the research correspond to the norms suggested in literature sources.